Case for Medical Physiology Small-Group Discussion: Atrial Fibrillation - Rob Zachow; Carol Sadley; Joseph Schwenkler (Association of American Medical Colleges, 2007)
Abstract This resource uses a real clinical presentation in order to extend students' comprehension of medical physiology and integrate this knowledge with that obtained in other first-year courses, such as biochemistry, cellular and genetic mechanisms, neurophysiology, systems histology, and gross anatomy. In this manner, we have been able to evolve from more basic and relatively unchallenging question-and-answer oriented small-group sessions and stimulate the learning process within the small-group setting using clinical problems. This resource is an actual account of the author's experience. By adjusting the suggested topics for discussion, this case can be adapted for use in a variety of year-one and year-two medical school courses as well as other health professional curricula.